TOOLS AND SERVICES OF THE EUROPEAN OPEN SCIENCE CLOUD IN ORDER TO SUPPORT SCIENTIFIC AND EDUCATIONAL ACTIVITIES - Marienko, Maiia; Nosenko, Yulia; Shyshkina, Mariya (Physical and Mathematical Education, 2021)
The article analyzes the modern trends of the European space of open science, the essence and benefits of cloud-oriented tools and services of open science. Examples of services of the European Open Science Cloud are considered. Recommendations on qualitative and effective introduction of tools and services of open science in scientific and educational activities are provided. Problem formulation. The urgency of research is due to the need to improve the quality and effectiveness of the implementation of tools and services of open science in scientific and educational activities, increasing the efficiency of their use in national science and education system, improving the level of training of educational specialists, including teachers. Materials and methods. Theoretical methods were used to solve the tasks set in the work: analysis of scientific and pedagogical theories and concepts on the research problem; analysis and generalization of tendencies of the European space of open science; analysis of the functionality of cloud-based open science services. Results. The essence of the concept of a cloud-oriented system of open science is analyzed. The essence and significance of the European open science cloud is considered. The main trends that are currently prevailing in the European space of open science are defined: open access, archiving articles, data sharing. Examples of services of the European open science cloud are considered. Conclusions. Taking into account the modern trends of the European space of open science, the use of the advantages of cloud-oriented tools and services of open science, taking into account the author’s recommendations will contribute to improving the quality and the effectiveness of introduction in the educational process of tools and cloud computing services, wider use of open science services at different levels of study, improving the level of training of specialists of the educational sector.